A rare intestinal mucormycosis caused by Lichtheimia ramosa in a patient with diabetes: a case report - Liu, Qinqin; Chen, Ping; Xin, Li; Zhang, Jiahao; Jiang, Meijie (Frontiers in Medicine, 2024)
Mucormycosis is an aggressive fungal disease. Gastrointestinal mucormycosis is rare, but its clinical symptoms lack specificity and mortality is high. Here, we report a case of intestinal mucormycosis caused by Lichtheimia ramosa in a 65-year-old woman with diabetes mellitus. The patient exhibited extensive mucosal tissue damage in the colon, with broad, undivided filamentous fungal hyphae present in the intestinal tissue. Therefore, the patient was suspected to have a filamentous fungal infection. Colonic tissue samples were obtained for fungal culture, and the fungus was identified as L. ramosa based on morphology and DNA sequencing. This case highlights the importance of pathologists and microbiologists in identifying pathogenic fungi and the significance of screening for mucormycosis in high-risk patient populations.